Efficacy of music intervention on pain and anxiety in patients undergoing cataract surgery: a systematic review and meta-analysis - Su, Lanzhu; Zhang, Yuanyuan; Lu, Lixin (Frontiers in Psychiatry, 2025)
ObjectiveTo evaluate the effectiveness of music therapy in reducing anxiety and pain among patients undergoing cataract surgery.MethodsRelevant studies up to May 2024 were identified by searching PubMed, Embase, Cochrane, Web of Science, CNKI, and Wanfang databases. Literature selection followed PICOS criteria, with methodological quality assessed using the Cochrane risk of bias tool. Meta-analysis employed standardized mean differences (SMD). Sensitivity and subgroup analyses explored result stability and heterogeneity, utilizing Review Manager 5.4 and STATA 15.0 for analysis.ResultsEighteen studies with 2,262 participants were included. Music therapy significantly reduced anxiety levels, as demonstrated by a notable decrease in Visual Analog Scale (VAS) anxiety scores (SMD = -7.10, 95% CI: -12.25 to -1.95) and State-Trait Anxiety Inventory (STAI) scores (SMD = -1.26, 95% CI: -1.85 to -0.66). Self-Rating Anxiety Scale (SAS) scores were also significantly lower in the music therapy group (SMD = -0.27, 95% CI: -0.42 to -0.12). Regarding physiological parameters, music therapy significantly reduced systolic blood pressure (SBP) (SMD = -0.58, 95% CI: -0.80 to -0.35), diastolic blood pressure (DBP) (SMD = -0.27, 95% CI: -0.42 to -0.12), and heart rate (HR) (SMD = -0.31, 95% CI: -0.45 to -0.17). Subgroup analysis indicated greater therapeutic efficacy among Asian populations compared to European populations.ConclusionMusic therapy significantly reduces anxiety and pain in cataract surgery patients and improves vital signs to some extent. However, due to heterogeneity in certain results, further high-quality randomized controlled trials (RCTs) are needed to confirm its effectiveness.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024586504.